Angiotensin II antagonists in heart failure – current recommendations - Grabowski, Marcin; Filipiak, Krzysztof J.; Opolski, Grzegorz (Przewodnik Lekarza/Guide for GPs, 2005)
Current guidelines of European Society of Cardiology on treatment of heart failure with the use of angiotensin II receptor antagonists are presented in this article.